Synthesis, in vitro biological assessment, and molecular docking study of benzimidazole-based thiadiazole derivatives as dual inhibitors of α-amylase and α-glucosidase - Khan, Shoaib; Iqbal, Shahid; Taha, Muhammad; Hussain, Rafaqat; Rahim, Fazal; Shah, Mazloom; Awwad, Nasser S.; Ibrahium, Hala A.; Alahmdi, Mohammed Issa; Dera, Ayed A.; Ullah, Hayat; Bahadur, Ali; et al. (Frontiers in Chemistry, 2023)
The clinical significance of benzimidazole-containing drugs has increased in the current era, making them more effective scaffolds. These moieties have attracted researchers' strong interest because of their diverse biological features. In order to examine various biological significances, a number of research synthetic methodologies have recently been established for the synthesis of benzimidazole analogues. In this work, an effort was made to efficiently and quickly synthesis a new series of benzimidazole analogues. Numerous spectroscopic techniques, including as 1H-NMR, 13C-NMR, and HREI-MS, were used to confirm all of the synthesized compounds. Molecular docking experiments were also carried out to verify how the compounds interacted with proteins. To explore the inhibitory activity of analogues against α-amylase and α-glucosidase, all derivatives (1–17) were assessed for their biological potential. When compared to the reference drug acarbose (IC50 =8.24 ± 0.08 µM), almost all derivatives were determined to be exhibiting highly promising activity. Among the tested series analogue 2 (IC50 = 1.10 ± 0.10 and 2.10 ± 0.10 µM respectively), displayed better inhibitory activity.